Chapter Violence and Politics in Zimbabwe from 2008-2018 - Raleigh, Clionadh (Oxford University Press, 2020)
"Zimbabwe's ZANU-PF party has been locked in an internal battle of political survival which intensified as the country democratized. Political violence has become a common feature in these internal struggles and underscores the degree of competition between agents within the government. This analysis of Zimbabwe's political violence is presented in three sequential parts: the first considers patterns and explanations for the violence in 2008; the second on subsequent low-level violence since 2008; and the last on the violence emanating from internal ZANU-PF factional struggles. There are continuities in this violence over the past ten years; first, the politics of the ruling party have become the defining feature of the Zimbabwean state; and political violence remains a direct reflection of ZANU-PF internal struggles. Second, violence is most intense surrounding elections. Violence marred all three that took place between January 2008 and August 2018, although at vastly different rates and in response to different perceived threats. Despite the repeated risks of violence during elections, Zimbabwe remains a relatively stable country with low rates of all political violence compared to the surrounding states in Africa. Third, violence is but one way that the internal competition with ZANU-PF and state institutions is performed. As ZANU-PF continues to alter its foundations, elites and principles to be 'fit for purpose', there are reasons to believe that violence rates will not change."